Human Sperm Chromatin Maturation: A Study of Prolactin Supplementation in Sperm Preparation - Silvia W Lestari (Journal of Global Pharma Technology, 2020)
One of the management of infertile couples is assisted reproduction through the Intra Uterine Insemination (IUI). Paternal factor has been known to influence the success of IUI, such as sperm selection on preparation. Prolactin (PRL) is reported to select sperm with better DNA fragmentation on the preparation process. This study aimed to investigate sperm selection with better chromatin maturation quality, by the supplementation of PRL. Semen samples were obtained from 10 infertile men who experienced sperm preparation for IUI. Prepared sperm were incubated at 1000 ng/ml of PRL, followed by chromatin maturation test. Its index was determined as mature sperms in 100 sperms. The differences in sperm chromatin maturation showed a significant difference (p